Air purification system for a window - LEE EUN JUNG; LEE, GYEONG MO; LEE DONG YOUP (2023)
Disclosed is a window air purification system. The window air purification system of the present invention includes: a window frame including a base part forming a lower end part, a pair of side parts extended from both sides of the base part, a window frame disposed in an upper area of the base part with a top part connecting the pair of side parts, and a window opening and closing the window frame; an air inlet/outlet part provided on a wall on the inside of the top part, and forming a place to introduce purified air indoors or discharge contaminated air from the inside to the outside; and an air purification part provided in the window frame of the window, and purifying the outside air and guiding the air to be introduced indoors through the air inlet/outlet part or guiding the contaminated air from the inside to be discharged to the outside through the air inlet/outlet part. Therefore, the present invention is capable of always maintaining a pleasant indoor environment in a building. 창호용 공기정화 시스템이 개시된다. 본 발명의 창호용 공기정화 시스템은 하단부를 이루는 베이스부와, 상기 베이스부의 양측에서 연장되는 한 쌍의 사이드부와, 상기 베이스부의 상부 영역에 배치되되 한 쌍의 상기 사이드부를 연결하는 탑부를 구비하는 윈도 프레임(window frame)과, 상기 윈도 프레임을 개폐하는 윈도(window)를 구비하는 창호; 상기 탑부의 실내 측 벽체에 마련되며, 정화공기를 실내로 유입시키거나 실내의 오염공기가 실외로 배출되는 장소를 형성하는 공기 유출입부; 및 상기 창호의 윈도 프레임에 마련되며, 실외 공기를 정화시켜 상기 공기 유출입부를 통해 실내로 유입되게 하거나 실내 오염공기가 상기 공기 유출입부를 통해 실외로 배출되게 가이드하는 공기정화부를 포함한다.